2004
DOI: 10.1094/mpmi.2004.17.6.686
|View full text |Cite
|
Sign up to set email alerts
|

Swimming Motility, a Virulence Trait of Ralstonia solanacearum, Is Regulated by FlhDC and the Plant Host Environment

Abstract: Swimming motility allows the bacterial wilt pathogen Ralstonia solanacearum to efficiently invade and colonize host plants. However, the bacteria are essentially nonmotile once inside plant xylem vessels. To determine how and when motility genes are expressed, we cloned and mutated flhDC, which encodes a major regulator of flagellar biosynthesis and bacterial motility. An flhDC mutant was nonmotile and less virulent than its wild-type parent on both tomato and Arabidopsis; on Arabidopsis, the flhDC mutant also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
77
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 36 publications
1
77
0
Order By: Relevance
“…Control of flagella and chemotaxis is exercised through the master operon flhDC (Macnab, 1996). Salmonella flhDC mutants are defective in invasion of in vitro cultured epithelial cells due to their lack of motility (Schmitt et al, 2001;Young et al, 2000) and a role in virulence for these genes has been shown in other bacteria (Givaudan & Lanois, 2000;Tans-Kersten et al, 2004). However, a S. enterica serovar Typhimurium flhDC mutant is not attenuated (Fig.…”
Section: S Enterica Serovar Typhimurium Rcsc Mutants With Constitutimentioning
confidence: 99%
“…Control of flagella and chemotaxis is exercised through the master operon flhDC (Macnab, 1996). Salmonella flhDC mutants are defective in invasion of in vitro cultured epithelial cells due to their lack of motility (Schmitt et al, 2001;Young et al, 2000) and a role in virulence for these genes has been shown in other bacteria (Givaudan & Lanois, 2000;Tans-Kersten et al, 2004). However, a S. enterica serovar Typhimurium flhDC mutant is not attenuated (Fig.…”
Section: S Enterica Serovar Typhimurium Rcsc Mutants With Constitutimentioning
confidence: 99%
“…For complementation studies, a 12-kb EcoRI fragment containing the intact cheA and cheW genes was subcloned into pSTBlue-1 from R. solanacearum strain K60 genomic library cosmid 2-89, which contains a large cluster of motility and taxis genes (50,52), to create pSJYcheYAW12.0. The 12-kb insert of pSJYcheYAW12.0 was transferred into pBluescript II SK(Ϫ) with BamHI-HindIII to create pBJYcheYAW12.0.…”
mentioning
confidence: 99%
“…Active PhcA is regulated in response to cell density by a quorum-sensing mechanism that involves the specific autoinducer molecule 3-hydroxy palmitic acid methyl ester (3-OH PAME) (Flavier et al 1997). At a low cell density, presumably corresponding to saprophytic life and early plant colonization, PhcA is not expressed in culture, leading to expression of early disease virulence factors, including several polygalacturonases and both twitching and swimming motility (Liu et al 2001;Kang et al 2002;Tans-Kersten et al 2004). At a later stage of infection, at a high cell density, the accumulation of 3-OH PAME leads to activation of PhcA and, subsequently, production of EPS and activation of potent CWDEs (cellulases and pectin methylesterase).…”
mentioning
confidence: 99%